Making Political Tourism As an Alternative Model for Hawaii Indigenous Development - Wilmar Salim (ASEAN Journal on Hospitality and Tourism, 2012)
The current tourism business model, which is visitor-centered, shows how tourism has strong negative impacts to the host and the place. It happens in many places in the world where tourism business is run by outsiders or with outside capital, and creating conflict with local population. Political tourism is an alternative to the current business model because it looks at the business from the other side: the host-place-centered. Political tourism can be seen as the first step in "indigenizing" capitalism based on local values. The proposed model addresses subsystems in tourism business components, i.e. the transaction, transfer, and treatment systems. It suggests several strategies to make political tourism happen with reference to Native Hawaiians tourism development. It offers some lessons that can be applicable to other places in Asia and the Pacific.